CONTRIBUTION OF CORN FARMING BUSINESS IN IMPROVING COMMUNITY ECONOMIC WELFARE (CASE STUDY OF BUN ALAS VILLAGE, LEUSER DISTRICT, SOUTHEAST ACEH REGENCY): KONTRIBUSI USAHA PERTANIAN JAGUNG DALAM PENINGKATAN KESEJAHTERAAN EKONOMI MASYARAKAT (STUDI KASUS DESA BUN ALAS KECAMATAN LEUSER KABUPATEN ACEH TENGGARA) - Alfarisi, Salman; Henderlan Harahap, Lutfi; Khaira Sihotang, Mutiah (LPPM UPMI, 2023)
This study aims to determine the driving and inhibiting factors of corn farming to the household economy in Bun Alas Village and the contribution of corn farming to the household economy of farmers in Bun Alas Village. This research uses a qualitative approach with case studies. 15 corn farmers were selected as key research informants. The results of the study show that corn farming is proven to make a good contribution to the economic welfare of the community, this is evidenced by the sufficient necessities of life for them and being able to provide education costs for their children in Bun Alas Village, this cannot be separated from the supporting factors, namely: corn farmers in Bun Alas Village, sufficient workers, and the land is quite wide and fertile, while the inhibiting factors are: limited capital, damaged transportation roads, and lack of knowledge in eradicating pests, especially pigs and monkey. In addition, the role of farmer groups is to contribute to farmers, because with farmer groups, agricultural facilities from the government can be channeled through corn farmer group administrators such as: Seeds and government subsidized fertilizers.